NEW APPROACHES TO UNDERSTANDING THE ADMINISTRATIVE JUSTICE - Тихомиров, О. Д.; Гусарєва, О. С. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2009)
In the article are analyzed different scientific approaches of understanding of administrative justiceon the examples of theoretical-legal researches of the separate Ukrainian and Russian workersof researches, that will become basis for forming of more developed methodology of scientific cognition of institute of administrative justice.